Interfacial spin glass state and exchange bias in manganite bilayers with competing magnetic orders - Tendeloo, G. Van (2014)
The magnetic properties of manganite bilayers composed of G-type antiferromagnetic (AFM) SrMnO3 and double-exchange ferromagnetic (FM) La0.7Sr0.3MnO3 are studied. A spin-glass state is observed as a result of competing magnetic orders and spin frustration at the La0.7Sr0.3MnO3/SrMnO3 interface. The dependence of the irreversible temperature on the cooling magnetic field follows the Almeida-Thouless line. Although an ideal G-type AFM SrMnO3 is featured with a compensated spin configuration, the bilayers exhibit exchange bias below the spin glass freezing temperature, which is much lower than the Néel temperature of SMO, indicating that the exchange bias is strongly correlated with the spin glass state. The results indicate that the spin frustration that originates from the competition between the AFM super-exchange and the FM double-exchange interactions can induce a strong magnetic anisotropy at the La0.7Sr0.3MnO3/SrMnO3 interface.